Pelatihan Strategi Pemasaran Digital UMKM: Dari Dapur Lokal Menuju Pasar Global - Miftahus Surur; Arico Ayani Suparto; Raudatul Jannah; Budiyanto Budiyanto; Fairous Shafira Huda; Nanda Nur Aini; Dendy Mangkuwiraja Irwandana Putra (Universitas Muhammadiyah Manado, 2026)
The acceleration of digital transformation and business legality has become an urgency for the economic resilience of rural MSMEs in the Industry 4.0 era. However, food-crafting MSMEs in Kedungdowo Village, Situbondo, experience market reach stagnation due to low digital literacy, reliance on reactive conventional marketing, and a lack of formal business permits. This community service aims to transform the partners' business ecosystem through the Asset-Based Community Development (ABCD) approach to break the deficit mentality and incubate business independence. The structured implementation consisted of local asset identification, financial governance training, marketing digitalization, and door-to-door legality mentoring. Intervention results demonstrate a measurable increase in operational capabilities. In absolute terms, 100% (10 MSMEs) successfully adopted WhatsApp Business and Google Maps as their digital storefront infrastructure. Furthermore, institutional legitimacy increased significantly, with 100% of partners securing a Business Identification Number (NIB) and 60% obtaining Home Industry Food (P-IRT) permits. This digital transformation, the application of intellectual honesty-based copywriting techniques, and the improvement in Cost of Goods Sold (COGS) governance precision directly correlated to an average sales volume surge of 35% post-intervention. In conclusion, the harmonious integration of technological acceleration, managerial and financial literacy, and legal compliance proved crucial and effective in shifting the mindset of rural MSMEs from mere informal entities to a resilient, responsive, and sovereign digital business ecosystem amid disruption.